Assessment of the speed of transmission of Ehrlichia canis, Anaplasma phagocytophilum, and Borrelia burgdorferi sensu stricto by infected ticks through an in vitro experimental model - F. Beugnet; M. Madder; A. Joubert; I. Bouzaidi Cheikhi; M. Chajia; J. F. Besselaar; D. Y. Tan (Parasites & Vectors)
Abstract Background Canine vector-borne diseases (CVBDs) have significant clinical and public health implications. Methods This experimental study used a validated continuous-flow in vitro feeding system (CFIFS) to investigate the speed of transmission (SOT) of three tick-borne pathogens (TBPs): Ehrlichia canis by laboratory-infected Rhipicephalus sanguineus (18.3% infection rate), Anaplasma phagocytophilum by laboratory-infected Ixodes ricinus (56%), and Borrelia burgdorferi sensu stricto (s.s.) by laboratory-infected I. ricinus (76%). Three experiments were conducted, one per pathogen/tick model. A total of 58–60 ticks were used per feeding system. Four to six replicates were obtained per experiment. All ticks were laboratory-reared. The tick infections were performed by feeding the nymphal stages on infected hosts. Results All ticks began to attach and feed 3 h after being introduced to the feeding system. At the maximum attachment, 89.7% of R. sanguineus were attached at 57 h, with 4–30% attachment at 51 h for I. ricinus infected with A. phagocytophilum, and 6.3–47.9% at 48 h for I. ricinus infected with B. burgdorferi s.s. Polymerase chain reaction (PCR) tests were used to detect the presence of pathogens from blood samples collected every 3 h. Swab samples from the inner face of the feeding membrane were also collected and tested every 6 h during the B. burgdorferi s.s. study. In this experimental in vitro design, after the first tick attachments were observed, E. canis exhibited SOT of 3–6 h, A. phagocytophilum of 12–15 h, and B. burgdorferi of 42–45 h in blood but only 3–6 h on inner membrane swabs. Conclusions The findings of this in vitro study highlight the transmission time of some TBPs, confirming previous data obtained in vitro or in vivo, by using the same design for all tick/pathogen models. This is a way to estimate the possibility of using acaricidal drugs to block pathogen transmission based on the SOT and the speed of kill of these compounds. Graphical Abstract